Arabic Methaphor and Idiom in Translation - Menacere, Mohammed (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1992)
SummaryThis paper attempts to discuss the problems of translating Arabic discourse involving specific cultural concepts. Cultural differences besides linguistic complexities constitute areas of potential difficulties in translating Arabic into English. These difficulties arise when one form of behaviour in one culture is virtually non-existent in another, or when the same cultural concept is conceived and interpreted differently by both cultures. The paper also considers the degree to which Arabic metaphors and idioms may be preserved in English translation.